Long-chain polyunsaturated fatty acid status in children, adolescents and adults with phenylketonuria. (June 2016) - Gramer, Gwendolyn; Haege, Gisela; Langhans, Claus-Dieter; Schuhmann, Vera; Burgard, Peter; Hoffmann, Georg F.
Abstract: Background: Patients with phenylketonuria have been reported to be deficient in long-chain polyunsaturated fatty acids (LCPUFAs). It has been postulated that good compliance with the dietary regimen negatively influences LCPUFA status. Methods: In 36 patients with phenylketonuria and 18 age-matched healthy control subjects LCPUFA-levels in plasma phospholipids and cholesteryl esters, erythrocyte phosphatidylcholine and phosphatidylethanolamine were evaluated. Results: Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) levels did not differ significantly between patients and control subjects in plasma and erythrocyte fractions. There was a significant negative correlation between SDS (standard deviation) scores of DHA-levels in erythrocyte parameters from the respective age-matched control group and patients' concurrent and long-term phenylalanine levels for erythrocyte phosphatidylethanolamine and erythrocyte phosphatidylcholine. Patients with lower (higher) phenylalanine levels had positive (negative) DHA-SDS. Conclusion: In contrast to previous reports we did not find lower LCPUFA-levels in patients with phenylketonuria compared to age-matched healthy control subjects. Good dietary control was associated with better LCPUFA status. Highlights: In patients with phenylketonuria LCPUFA deficiency has been reported. Good dietary compliance has been postulated to negatively influence LCPUFA status. LCPUFA status was evaluated in patients with phenylketonuria from three age groups. LCPUFAs in patients with phenylketonuria were not lower than in control subjects. Good dietary control was associated with better LCPUFA status.